Survival of the weakest? Culling evidence from the 1918 flu pandemic - Joël Floris; Laurent Kaiser; Harald Mayr; Kaspar Staub; Ulrich Woitek (University of Zurich, Department of Economics, 2019)
When a negative shock affcts a cohort in utero, two things may happen: first, the population suffers detrimental consequences in later life; and second, some will die as a consequence of the shock, either in utero or early in life. The latter effect, often referred to as culling, may induce a bias in estimates of later life outcomes. When the health shock disproportionately affects a positively selected subpopulation, the long-term effects are overestimated. The 1918 flu pandemic was plausibly more harmful to mothers of high socioeconomic status, as a suppressed immune system in mothers of low socioeconomic status may have been protective against the most severe consequences of infection. Using historical birth records from the city of Bern, Switzerland, we assess this concern empirically and document that a careful consideration of culling is paramount for the evaluation of the 1918 flu pandemic and other fetal health shocks.
Keywords: I10; I15; I18; N34; J24; 330; fetal origins hypothesis; 1918 flu pandemic; culling; survivorship bias